(untitled) (Nigerian Dental Journal, 2010)
Objective: The study was carried out to assess the oral hygiene status and to determine the prevalence of gingival and periodontal diseases in 10-12-year-old school children in Sholapur City, India. Method: A total of 1045 children (560 boys and 485 girls) aged 10-12 years were evaluated by questionnaires related to oral hygiene practices and clinical examination using Simplified Oral Hygiene Index (OHI-S) , Gingival Index and Russell’s Periodontal index. Result: All the children examined irrespective of the gender brushed their teeth with tooth brush and tooth paste. A total of 940 (90%) children brushed their teeth once in a day, while the remaining 105 (10%) brushed twice daily. Prevalence of gingival disease was 81% and males were more affected than females. Ten year old children were affected most by gingivitis. Good oral hygiene status was seen in 30% of total population examined, 2% had poor oral hygiene status and others (68%) showed fair oral hygiene status. Fifteen percent of the children had mild gingivitis, 64% had moderate gingivitis and 1% had severe gingivitis. Pockets were absent in all the children. Conclusion: There was a high prevalence of gingival disease in the population examined in this study, indicating the need for community health activities and awareness programme to improve the oral health of the people in this particular stratum of population.